An equatorial contractile mechanism drives cell elongation but not cell division. - Ivonne M Sehring (Public Library of Science (PLoS), 2014)
Cell shape changes and proliferation are two fundamental strategies for morphogenesis in animal development. During embryogenesis of the simple chordate Ciona intestinalis, elongation of individual notochord cells constitutes a crucial stage of notochord growth, which contributes to the establishment of the larval body plan. The mechanism of cell elongation is elusive. Here we show that although notochord cells do not divide, they use a cytokinesis-like actomyosin mechanism to drive cell elongation. The actomyosin network forming at the equator of each notochord cell includes phosphorylated myosin regulatory light chain, α-actinin, cofilin, tropomyosin, and talin. We demonstrate that cofilin and α-actinin are two crucial components for cell elongation. Cortical flow contributes to the assembly of the actomyosin ring. Similar to cytokinetic cells, membrane blebs that cause local contractions form at the basal cortex next to the equator and participate in force generation. We present a model in which the cooperation of equatorial actomyosin ring-based constriction and bleb-associated contractions at the basal cortex promotes cell elongation. Our results demonstrate that a cytokinesis-like contractile mechanism is co-opted in a completely different developmental scenario to achieve cell shape change instead of cell division. We discuss the occurrences of actomyosin rings aside from cell division, suggesting that circumferential contraction is an evolutionally conserved mechanism to drive cell or tissue elongation.